2019
DOI: 10.1017/bec.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Work Ability in Individuals With a Common Mental Disorder: Is There an Effect of Metacognitive Beliefs Among Poor Physical Health and Emotional Distress?

Abstract: Work ability is a prospective predictor of sick leave, disability pension and unemployment, and has been defined as the balance between human resources and the demands of work, taking into consideration that illness is not equivalent to work disability. In the present study we set out to explore predictors of work ability in a sample of individuals with common mental disorders. In particular, we were interested in exploring metacognitive beliefs as a potential predictor of work ability, as Wells’ (2009) metaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Thus, there seem to be a role for metacognitions to work ability beyond more objective indicators such as health status. This finding is in line with a previous cross-sectional study that reported an association between metacognitions and work ability beyond physical health status and emotional distress symptoms (Nordahl & Wells, 2019b), but our findings add to this study by demonstrating a prospective effect from metacognitions to work ability. Furthermore, our modeling approach incorporates a within-person effect of metacognitions, such that its effect alters an individual's work ability change trajectory.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, there seem to be a role for metacognitions to work ability beyond more objective indicators such as health status. This finding is in line with a previous cross-sectional study that reported an association between metacognitions and work ability beyond physical health status and emotional distress symptoms (Nordahl & Wells, 2019b), but our findings add to this study by demonstrating a prospective effect from metacognitions to work ability. Furthermore, our modeling approach incorporates a within-person effect of metacognitions, such that its effect alters an individual's work ability change trajectory.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent cross-sectional study, Nordahl and Wells (2019a) reported a positive correlation between dysfunctional metacognitions and self-reported work ability and showed that metacognitive beliefs in the form of judgements of memory confidence accounted for independent variance in work ability even when controlling for the effects of physical health status and emotional distress symptoms in individuals with a diagnosed common mental disorder. Other studies have indicated that dysfunctional metacognitive beliefs correlate with work status (Nordahl & Wells, 2019b and that, dysfunctional metacognitions are prospective predictors of return-to-work (RTW) in patients with chronic pain, chronic fatigue, and emotional disorders (Jacobsen et al, 2020). There is also evidence suggesting that Metacognitive therapy (Wells, 2009), which aims to modify dysfunctional metacognitive knowledge is associated with RTW in patients with Major Depressive Disorder (Solem et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to negative metacognitive beliefs resulting from adverse experiences in childhood that are associated with high levels of depression. Researchers have found that a low confidence in one's own memory was associated with low work ability ( 41 ). When adjusting in a structural equation model, the significant associations for depression were lowest for working a blue-collar job and highest for being currently unemployed.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focuses on how patients experience MCT and work interventions as an integrated part of psychological treatment for CMD. MCT is a relatively new treatment for depression and anxiety [15]. The results are promising and possibly even superior to those of other treatment methods [16].…”
Section: Introductionmentioning
confidence: 99%